2021
DOI: 10.1186/s11671-021-03586-z
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Driven Photoelectrochemical Performance of Novel ZnO/Ag2WO4/AgBr Nanorods-Based Photoelectrodes

Abstract: Highly efficient photoelectrochemical (PEC) water oxidation under solar visible light is crucial for water splitting to produce hydrogen as a source of sustainable energy. Particularly, silver-based nanomaterials are important for PEC performance due to their surface plasmon resonance which can enhance the photoelectrochemical efficiency. However, the PEC of ZnO/Ag2WO4/AgBr with enhanced visible-light water oxidation has not been studied so far. Herein, we present a novel photoelectrodes based on ZnO/Ag2WO4/Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Adam et al reported about Ag/Ag 2 WO 4 as promising candidate for optimal use of sunlight, which provides a higher photocurrent of 3 mA cm −2 measured at 1.23 V (vs. Ag/AgCl) for ZnO/Ag/Ag 2 WO 4 , which is 3 times the photocurrent achieved by ZnO nanorods [115]. Mustafa, with co-authors, demonstrated the exploitation of nanoplasmonic Ag to prepare a photoanode of ZnO/Ag 2 WO 4 /AgBr, which exhibits a photocurrent density five times greater than bare ZnO nanorod-based photoanode (Figure 7) [116].…”
Section: Modification Of Zno For the Water-splitting Reactionmentioning
confidence: 90%
“…Adam et al reported about Ag/Ag 2 WO 4 as promising candidate for optimal use of sunlight, which provides a higher photocurrent of 3 mA cm −2 measured at 1.23 V (vs. Ag/AgCl) for ZnO/Ag/Ag 2 WO 4 , which is 3 times the photocurrent achieved by ZnO nanorods [115]. Mustafa, with co-authors, demonstrated the exploitation of nanoplasmonic Ag to prepare a photoanode of ZnO/Ag 2 WO 4 /AgBr, which exhibits a photocurrent density five times greater than bare ZnO nanorod-based photoanode (Figure 7) [116].…”
Section: Modification Of Zno For the Water-splitting Reactionmentioning
confidence: 90%
“…There has been extensive use of silver-based semiconductors such as silver bromide (AgBr), silver chloride (AgCl), and silver tungstate (Ag2WO4) in nanostructured materials (e.g., ZnO, CuO, Ta2O5, etc.) [92][93][94][95][96] in order to enhance their visible light response and charge separation, which is due to their surface plasmon resonance (SPR)…”
Section: Silver-based Semiconductorsmentioning
confidence: 99%
“…and other properties as listed in Table 2.9. The addition of silverbased semiconductors can be managed by different methods (e.g., SILAR, hydrothermal, precipitation) [93,[96][97][98]. preparation of colloidal particles such as silica, Au-silica-core-shell, and Au-metal particles.…”
Section: Silver-based Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 In recent years, the deposition of silver tungsten oxide or silver tungstate (Ag 2 WO 4 ) nanoparticles by using a successive ionic layer adsorption and reaction (SILAR) method with various cycles onto metal oxide semiconductors with improved performance has been reported. [43][44][45][46][47] The SILAR method allows controlling the thickness of the deposition based on solution concentration and cycle number up to micrometers. 48 First, hydrothermal method was used to deposit nanoleaves of CuO.…”
Section: Introductionmentioning
confidence: 99%